The Cajal body: a meeting place for spliceosomal snRNPs in the nuclear maze - Stanek, David; Neugebauer, Karla M (Chromosoma, 2006)
Spliceosomal small nuclear ribonucleoprotein particles (snRNPs) are essential pre-mRNA splicing factors that consist of small nuclear RNAs (snRNAs) complexed with specific sets of proteins. A considerable body of evidence has established that snRNP assembly is accomplished after snRNA synthesis in the nucleus through a series of steps involving cytoplasmic and nuclear phases. Recent work indicates that snRNPs transiently localize to the Cajal body (CB), a nonmembrane-bound inclusion present in the nuclei of most cells, for the final steps in snRNP maturation, including snRNA base modification, U4/U6 snRNA annealing, and snRNA-protein assembly. Here, we review these findings that suggest a crucial role for CBs in the spliceosome cycle in which production of new snRNPs--and perhaps regenerated snRNPs after splicing--is promoted by the concentration of substrates in this previously mysterious subnuclear organelle. These insights allow us to speculate on the role of nuclear bodies in regulating the dynamics of RNP assembly to maintain a functional pool of factors available for key steps in gene expression.
Keywords: jaderné proteiny; Nuclear Proteins; RNA malá jaderná; Ribonucleoproteins, Small Nuclear; Cajalova tělíska; posttranskripční úpravy RNA; sestřih RNA; RNA Processing, Post-Transcriptional; Models, Biological; histony; Spliceosomes; Histones; zvířata; Humans; RNA, Small Nuclear; Coiled Bodies; biologické modely; ribonukleoproteiny malé jaderné; RNA Splicing; lidé; spliceozomy; Animals